Poly(I:C) and R848 ligands show better adjuvanticity to induce B and T cell responses against the antigen(s) - Nikunj Tandel; Digna Patel; Mansi Thakkar; Jagrut Shah; Rajeev K. Tyagi; Sarat K. Dalai (Heliyon, 2024)
Poly(I:C) and R848, synthetic ligands that activate Toll-like receptor 3 (TLR3) and TLR7/8 respectively, have been well-established for their ability to stimulate the immune system and induce antigen-specific immune responses. These ligands are capable of inducing the production of cytokines and chemokines, and hence support the activation and differentiation of B and T cells. We saw the long-lasting and perdurable immune responses by these adjuvants essentially required for an efficacious subunit vaccine. In this study, we investigated the potential of poly(I:C) and R848 to elicit B and T cell responses to the OVA antigen. We assessed the stimulatory effects of these ligands on the immune system, their impact on B and T cell activation, and their ability to enhanced generation of B and T cells. Collectively, our findings contribute to the understanding how poly(I:C) and R848 can be utilized as an adjuvant system to enhance immune responses to protein-based subunit vaccines. In the end, this work provides insights for the development of novel vaccination strategies and improving the vaccine efficacy. Present work shall help formulate newer strategies for subunit vaccines to address the infectious diseases.